08.12 Activated human b cells modulate cytokine production and differentiation of multipotent mesenchymal stromal cells. (1st March 2017) - Gitsioudis, Panagiotis; Resch, Bastian; Horn, Patrick; Saffrich, Rainer; Tykocinski, Lars; Lorenz, Hanns-Martin; Tretter, Theresa
Abstract : Background: Multipotent mesenchymal stromal cells (MSC) are well known for their multilineage potential and immunosuppressive properties. They might be a useful alternative for treatment of chronic inflammatory diseases. Little is known however, in how far the inflammatory cellular environment eg, activated lymphocytes and their mediators might interfere with their function. Aim of the study is to investigate the influence of activated B cells on immunologic and regenerative properties of MSC. Materials and methods: Highly purified CD19+B-cells were separated from PBMC by magnetic cell sorting. B-cells were polyclonally stimulated by B-cell-receptor cross-linking and IL-2 and cocultured with bone marrow derived MSC for various time periods. Cytokines were quantified after 72 hour by intracellular flow cytometry or in cell culture supernatants by ELISA and B cell division by flow cytometric methods at d5. Differentiation potential of MSC was assessed by use of established differentiation media in absence or presence of B cell culture supernatant. After 21 days differentiation into the osteogenic or adipogenic lineage was determined by fluorescence microscopy and quantified with ImageJ software. Results: In MSC-B-cell cocultures the MSC-specific production of IL-6 and IL-8 increased by more than 100-fold compared to MSC single cultures. In contrast, B cell-specific production of TNF-alpha, Immunoglobulins and B cell proliferation diminished in B-MSC cocultures by more than 50% suggesting an inhibitory feedback mechanism by activated MSC towards the B cells. Separation of B cells from MSC by semipermeable cell culture inserts (transwell) did not abolish observed effects, suggesting that soluble factors were the main mediators. Of note, addition of neutralising antibodies against the B cell specific cytokines TNF-alpha and IL-1-beta significantly reduced MSC cytokine production in cocultures. B cells also influenced regenerative potential of MSC: in presence of B-cell supernatant MSC differentiation into the osteogenic lineage was significantly increased, accompanied by higher cell number, while differentiation into the adipogenic lineage was inhibited. Conclusions: In presence of activated B cells MSC exert immunosuppressive effects.. However at the same time these MSC produce high amounts of proinflammatory cytokines and change their differentiation behaviour, suggesting an important influence of the cellular environment on MSC functions.